The Influence of Financial Literacy, and Investment Knowledge on Investment Interest mediated by Investment Motivation - Ni Putu Vera Juliati Pratiwi; I Nyoman Nugraha Ardana Putra; Raden Roro Dhi (Universitas Udayana, 2024)
This study attempted to determine the influence of investment knowledge and financialliteracy on capital market investing interest via investment motivation. All IDXInvestment Gallery users in the Faculty of Economics and Business, University ofMataram, made up the study's population, and 85 Investment Gallery users werechosen as the study's sample using a purposive selection approach. Associativequantitative research is the term used to describe this sort of study. Smart-PLS 4 wasutilized to process the data in this study, and the following tests were run: validity test,reliability test, R-Square, inner model, and path coefficient. The findings demonstratedthat, while investment knowledge has a negligible impact on investment interest,financial literacy, and investment motivation have a favorable and considerable impact.Investment motivation is positively and significantly impacted by financial knowledgeand literacy. Financial literacy and investment interest can be mediated by investmentmotive, but investment knowledge cannot.